Adsorption of Inorganic and Organic Waste of Chemistry Laboratory by Using Eggshell-based CaO - Karim, Kurnia Ramadani; Firnanelty, Firnanelty; Fadhilah, Nur (Indonesian Journal of Chemical Research, 2025)
Laboratory activities are closely related to using corrosive, acidic, and toxic chemicals in producing inorganic and organic waste, such as heavy metals, resulting from chemical reactions, and organic waste originating from ethanol solvents. Adsorption can be an appropriate waste handling step to reduce metal levels in waste. CaO can be used as an adsorbent through several mechanisms. One involves the basic nature of CaO, which forms ionic bonds with acidic compounds in the environment, so these molecules or ions can be adsorbed on the CaO surface. The aims are to characterize CaO and to determine the amount of adsorption power of the CaO catalyst on metals (Pb and Cd) and organic waste (ethanol) originating from the chemistry laboratory. The SSA measurement showed that the waste tested contained the highest levels of Cd and Pb metals, namely 16.82 ppm and 1.52 ppm. The adsorption results using CaO showed that the absorption capacity for Cd and Pb metal was up to 99%, while for ethanol, it was around 20%. It showed that CaO can be used as an adsorbent for laboratory waste.